Levels of organophosphate flame retardants and their metabolites among 391 volunteers in Taiwan: difference between adults and children - Cheng, Fu-Jen; Wang, Chih-Hwa; Pan, Hsiu-Yung; Chen, Chih-Cheng; Huang, Wan-Ting; Li, Shau-Hsuan; Wang, Liang-Jen; Wang, Chin-Chou; Lee, Wen-Chin; Tsai, Kai-Fan; Ou, Yu-Che; Kung, Chia-Te (Frontiers in Public Health, 2023)
Background Organophosphate flame retardants (OPFRs) are ubiquitous in the environment. The compositions and concentrations of different OPFRs metabolites vary in different environments depending on different human activities. The objective of the present study was to evaluate the exposure of different age groups to OPFRs in Taiwan. Methods Volunteers provided urine samples and responded to questionnaires including demographic factors, underlying disease, lifestyle information, and occupation from October 2021 to January 2022. OPFR measurements were performed using a Waters Acquity Ultra-Performance Liquid Chromatography system coupled with a Waters Xevo TQ-XS mass spectrometer. Results A total of 391 volunteers (74 children and 317 adults) were enrolled in this study. The concentrations (presented as μg/g creatinine) of bis(1,3-dichloro-2-propyl) phosphate (BDCPP, p = 0.029) and tri-n-butyl phosphate (TNBP, p = 0.008) were higher in the adult group, while the concentrations of bis-2-chloroethyl phosphate (BCEP, p = 0.024), diphenyl phosphate (DPHP, p < 0.001), tris(1,3-dichloro-2-propyl) phosphate (TDCPP, p = 0.009), and Tris(2-butoxyethyl) phosphate (TBEP, p = 0.007) were higher in the child group. Compared with school age children (>6 years), the concentration of di(2-n-butoxyethyl) phthalate (DBEP, 1.14 vs. 0.20 μg/g creatinine, p = 0.001), DPHP (1.23 vs. 0.54 μg/g creatinine, p = 0.036), TBEP (1.63 vs. 0.29 μg/g creatinine, p < 0.001), and the sum of OPFR metabolites (ΣOPFRs, 6.58 vs. 2.04 μg/g creatinine, p < 0.001) were statistically higher in preschool-aged children. After adjusting for confounding factors, pre-school age [odds ratio (OR): 4.579, 95% confidence interval (CI): 1.389–13.115] and current smoker (OR: 5.328, 95%CI: 1.858–14.955) were independently associated with the risk of ΣOPFRs higher than 90 percentile. Conclusion This study revealed the distribution of different OPFRs metabolites in children and adults. DBEP, DPHP, TBEP, and ΣOPFR were higher in preschool-aged children. Pre-school age and current smoking status were independent risk factors for ΣOPFRs higher than 90 percentile.